-6x-2x+13=-11

Simple and best practice solution for -6x-2x+13=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-2x+13=-11 equation:


Simplifying
-6x + -2x + 13 = -11

Reorder the terms:
13 + -6x + -2x = -11

Combine like terms: -6x + -2x = -8x
13 + -8x = -11

Solving
13 + -8x = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + -8x = -11 + -13

Combine like terms: 13 + -13 = 0
0 + -8x = -11 + -13
-8x = -11 + -13

Combine like terms: -11 + -13 = -24
-8x = -24

Divide each side by '-8'.
x = 3

Simplifying
x = 3

See similar equations:

| 3[x+2]+2x=7[x-1]+9 | | 5+0.1Q=20-0.2Q | | 2(4e)=35 | | 2=11-20 | | 3n^2-6n+8=0 | | 2y=37 | | 8y-6y-3=17 | | 6-18p= | | -5+8s-7+3s= | | 48=5w+8 | | 15x^2-2=0 | | -2(x+4)+8x=-14 | | 2z-6=10z+6 | | 2=-2(n-7) | | (3(42.5)+x+10)+(42.5+x)=180 | | 6y^2-2y-3=0 | | 5h+9+7h= | | 2(4e)=10 | | 13=3u-14 | | ln(x+3)=0.8 | | 0.666666666667x+6=0.5x+0.25x | | 2(4e)=90 | | 5+.1q=20-.2Q | | (3(42.5)+y+10)+(42.5+y)=180 | | 12+4(z-3)=-3z+6 | | 5w+11=96 | | 2x+2y+1+3x+1=180 | | (A+p)(a^2-ap+p^2)= | | 2(4e)=20 | | 24=4y-16 | | 2x+8+74+5x= | | 2(x+7)+3x=-4 |

Equations solver categories